2004
DOI: 10.1016/j.chembiol.2003.12.018
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of the Angiogenesis Inhibitor Borrelidin by Streptomyces parvulus Tü4055

Abstract: The biosynthetic gene cluster for the angiogenesis inhibitor borrelidin has been cloned from Streptomyces parvulus Tü4055. Sequence analysis indicates that the macrolide ring of borrelidin is formed by a modular polyketide synthase (PKS) (borA1-A6), a result that was confirmed by disruption of borA3. The borrelidin PKS is striking because only seven rather than the nine modules expected for a nonaketide product are encoded by borA1-A6. The starter unit of the PKS has been verified as trans-cyclopentane-1,2-dic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
107
0
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(112 citation statements)
references
References 42 publications
1
107
0
3
Order By: Relevance
“…Gene expression profiling of S. cerevisiae revealed that borrelidin up-regulated GCN4 leucine zipper mRNA synthesis (13), and this in turn induced the expression of amino acid biosynthetic enzymes. Because of its intriguing biological activities, the chemical synthesis (14,15) and biosynthesis (16) of borrelidin have been explored.…”
mentioning
confidence: 99%
“…Gene expression profiling of S. cerevisiae revealed that borrelidin up-regulated GCN4 leucine zipper mRNA synthesis (13), and this in turn induced the expression of amino acid biosynthetic enzymes. Because of its intriguing biological activities, the chemical synthesis (14,15) and biosynthesis (16) of borrelidin have been explored.…”
mentioning
confidence: 99%
“…To accomplish adipic acid biosynthesis through PKS engineering, we focused on the borrelidin PKS because it contains the only known loading AT domain that initiates polyketide biosynthesis with a carboxylated substrate (Figure 2a). 13 The proposed natural substrate based on the isolated borrelidin structure is trans-1,2-cyclopentanedicarboxylic acid (trans-1,2-CPDA) activated to its cognate CoA. Our studies indicated not only a requirement of the loading AT for substrates containing a terminal carboxyl moiety, but also that this loading didomain could use additional acidic substrates beyond trans-1,2-CPDA.…”
Section: Substrate Specificities Of Pks Domainsmentioning
confidence: 86%
“…25 The presumed natural substrate of the loading AT is trans-1,2-cyclopentanedicarboxylic acid (trans-1,2-CPDA) activated to its cognate CoA. 26 We have also demonstrated that the downstream protein BorA2 (KS-AT-KR-ACP) could accept the succinyl starter and extend with malonyl-CoA to produce 3-hydroxyadipic, attached to the ACP in BorA2. 25 This enzyme-bound product was released as a 3-hydroxyadipic acid by linking the erythromycin PKS TE domain immediately downstream of BorA2.…”
Section: Diacidsmentioning
confidence: 94%